Global air power - Olsen, John Andreas 1968- (Potomac Books, Inc, 2011)
Global Air Power provides insight into the evolution of air power theory and practice by examining the experience of six of the world's largest air forces-those of the United Kingdom, the United States, Israel, Russia, India, and China-and of representative smaller air forces in Pacific Asia, Latin America, and continental Europe. The chapters, written by highly regarded scholars and military leaders, explore how various nations have integrated air power into their armed forces and how they have applied air power in both regular and irregular warfare and in peacetime operations. They cover the organizational, professional, and doctrinal issues that air forces confronted in the past, the lessons learned from victory and defeat, and emerging challenges and opportunities